Effects of Void Array Orientation on Compressive Properties of Cellular Structures1 . Issue 10 (7th April 2017) - Dahm, Karl Laurence; McGavin, Peter Norman; Brown, Ian Willian Murray
Abstract : Additively manufactured cellular materials enable customized structural implants with superior osseointegration potential and mechanical properties better matched to bone. In this investigation, the compression response of Ti–6Al–4V alloy cellular materials comprising a simple cubic array of 2.00 mm diameter spherical voids with a 1.90 mm inter‐void spacing are studied. Finite element analysis (FEA) shows that the lattice exhibited cubic symmetry with values for Young's modulus (E), Poisson's ratio, and shear modulus in the range of 28.5–29.5 GPa, 0.18–0.20, and 5.4–6.0 GPa, respectively. Compression tests carried out on cylinders with the same cellular structure fabricated by selective laser melting also show a strong dependence of elastic and plastic properties on orientation. Compression normal to the 100 plane of the simple cubic cell gives the highest E and strength, while compression normal to the 110 and 111 planes give lower values. The experimental E values for the 100 and 111 orientations show good agreement with the FEA results, but the 110 orientation shows lower values of E compared to the FEA predictions. Ultimate compressive failure of the cylinders occurred by gross slip along the 100 planes of the void array – coinciding with the slip planes for the simple cubic system. Abstract : The mechanical properties of a cellular material comprising a simple cubic array of interconnected spherical voids show cubic elastic symmetry and therefore depend not only on the overall void content but also on the orientation of the applied load to the void array. Qualitatively, the mechanical response can be understood in terms of the 100 slip planes which have low shear strength and stiffness and provide a preferential failure plane as shown in the figure.